Edible films produced from agrifood by-products and wastes - Jorge, Alexandre M.S. (2023)
This study aims to develop edible films using agrifood by-products (pumpkin seeds, broken rice and orange pectin) and wastes (quince peel, potato peel, potato pulp, orange peel, pumpkin peel). The physicochemical characteristics of the films were investigated, including their mechanical and barrier properties. Higher amounts of plasticizer induced poorer mechanical and barrier properties in the films. The most promising ones were obtained with orange pectin, broken rice and pumpkin peel, with water contact angles (WCA) between 48° and 57°, maximum water vapor transmission rate and water vapor permeability of 575 g.m−2.d−1 and 108 × 10−12 g.Pa−1.s−1.m−1, respectively, Young's modulus between 350 and 800 MPa, maximum tensile strength between 9.0 and 26.25 MPa, and elongation at break between 2.28 and 9.3%. Orange pectin and broken rice are promising raw materials since they led to higher WCA, better barrier and mechanical properties. Broken rice and quince peel can be good substitutes for commercial starch and glycerol, respectively. Agro-industrial by-products and wastes revealed potential for the production of sustainable edible films.